Business choice, location decision and success of small and medium enterprises in Uganda - Kakooza, JohnBosco; Tusiime, Immaculate; Namiyingo, Sophia; Nabwami, Ruth; Basemera, Mellan (Emerald, 2023)
Purpose This paper aims to report on the results of a study carried out to establish the contribution of business choice and location decision to the success of small and medium enterprises in an emerging economy like Uganda. Design/methodology/approach This study is cross-sectional and correlational. Data were collected through a questionnaire survey of 181 small and medium restaurants. The data were analyzed through correlation coefficients and hierarchical regression using statistical package for social sciences. Findings The findings reveal that both business choice and location decisions positively and significantly contribute to the success of small and medium enterprises. However, it was noted that more attention should be paid to location decision than business choice as determinants of SME success. Originality/value To the authors' knowledge, this is the first study to investigate the contribution of business choice and location decision to the success of SMEs using evidence from a developing African country like Uganda. Finally, this research offers practical contributions to managers and owners of SMEs who have to make strategic decisions for firm profitability, survival and growth in the competitive business arena.